And Mama Studied with Me: Elementary Education, Modernization, Gendered Curricula, and the Reconfiguration of the Public and Private in the Danubian Principalities and Greek Lands, 1810s-1840s - Tipei, Alex R. (East European Politics and Societies: and Cultures, 2023)
This article argues that discussions about and plans for female education emerged in early nineteenth-century Southeast Europe in connection with broader programs of modernization. It suggests that when officials and educators in the early Greek state and Danubian Principalities created curricula for women, they seldom took regional realities or the needs of potential pupils into account. Rather, the courses of study they proposed more closely reflected the aspirations these regional elites had for their communities. The article explores how education helped (re)inscribe gender roles within modern institutions and allowed state officials and educators to formalize boundaries between the public and private spheres. Modernization, primary instruction, and gendered hierarchies were intimately related.